2015
DOI: 10.12659/ajcr.892804
|View full text |Cite
|
Sign up to set email alerts
|

Do Cinnamon Supplements Cause Acute Hepatitis?

Abstract: Patient: Female, 73Final Diagnosis: Drug induced acute hepatitisSymptoms: Abdominal pain • diarrhea • vomitingMedication: —Clinical Procedure: —Specialty: Gastroenterology and HepatologyObjective:Unusual or unexpected effect of treatmentBackground:The use of herbal medications to treat various diseases is on the rise. Cinnamon has been reported to improve glycolated hemoglobin and serum glucose levels. When patients consider the benefit of such substances, they are often not aware of potential adverse effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Of concern is a case report, which details a patient presenting with acute hepatitis after concomitantly taking rosuvastatin 40mg and cinnamon supplements for some undisclosed period of time. However the authors did not present which supplement and in what dose it was taken [44]. Unfortunately, no animal or human studies evaluating the long-term safety of cinnamon administration are available, and none of the studies we evaluated mentioned their subjects receiving statin therapy during the trial.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Of concern is a case report, which details a patient presenting with acute hepatitis after concomitantly taking rosuvastatin 40mg and cinnamon supplements for some undisclosed period of time. However the authors did not present which supplement and in what dose it was taken [44]. Unfortunately, no animal or human studies evaluating the long-term safety of cinnamon administration are available, and none of the studies we evaluated mentioned their subjects receiving statin therapy during the trial.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Ashraf et al [84] have confirmed that the combination of appropriate garlic extract ( Allium sativum L.) and metformin showed a significant reduction in fasting blood glucose compared to using alone metformin ( P < 0.05 ), and their study also reported that the interaction caused a significant decrease in the mean total cholesterol level ( P < 0.05 ). In contrast, a case study reported in 2015 showed that the combination of cinnamon and statins has the potential for significant liver damage and it should be discouraged [85], what’s more, in the theoretical point of view, concurrent use of cinnamon with blood sugar-lowering agents may have additive effects and increase the risk of hypoglycemia [86].…”
Section: Discussionmentioning
confidence: 99%
“…Cinnamon is obtained from different tree species of the genus Cinnamomum: Chinese cinnamon (Cinnamomum cassia or Cinnamomum aromaticum), coming from the East and containing high level of coumarin, with potential harmful effects [146]; and Ceylon cinnamon (Cinnamomum zeylanicum or Cinnamomum verum), coming from Sri Lanka and Madagascar, which contains only trace amounts of coumarin. Hepatotoxicity, effects of coumarin on coagulation and potential interference with drugs and mild adverse events have been reported for Chinese cinnamon, while, the consumption of Ceylon cinnamon seems safe [147][148][149].…”
Section: Toxicity and Reactivitymentioning
confidence: 99%